(untitled) (Journal of Comparative & International Higher Education, 2024)
This paper explores the impact of the Russia-Ukraine war on Russia’s academic sector, relying on the limited evidence available. The invasion has triggered an academic exodus from Russia, with immediate and far-reaching consequences. These consequences range from the interruption of ongoing research projects and termination of international collaborations to the emergence of an intellectual void, raising concerns about the future of academic pursuits in Russia. Conventional models for understanding academic mobility, which focus mainly on professional and economic incentives, prove inadequate in accounting for the complexities introduced by geopolitical strife, international sanctions, and curtailed academic freedoms. This paper calls for an interdisciplinary approach incorporating perspectives from political science, sociology, and international relations for a richer understanding of academic migration in conflict-affected settings. The Russia-Ukraine war serves as an important case study, shedding light on the vulnerabilities of academic sectors, even in the aggressor country where the physical conflict is not occurring, and offering broader insights for the field of academic mobility.